Portable pump tyre inflator / Adi Mustakim Ab Rahim and Nik Muhamad Syazwan Nek Omar - Ab Rahim, Adi Mustakim; Nek Omar, Nik Muhamad Syazwan (2015)
This is the summary of how our project work. This project is used a microcontroller PIC 16F877 A. The project is about how to interface the air compressor to the microcontroller. The air compressor need a 12 V and 10 amps supply to make sure air compressor running smoothly. From that, a car battery need to connect to air compressor . after the air compressor need to interface to the microcontroller to control by the switch. To do that, the transistor TIP142 is used to interface between air compressor and microcontroller. The air compressor is control by switch button. The process begin when the switch is tum on. The LCD display shows a pumping sign. Therefore, the air compressor will start pumping the tyre until it enough pressure. The LCD display will show not pumping sign if is switch tum off. The air compressor will not pumping if switch is tum off. The microcontroller also need a 5V. From that a voltage regulator LM705 l is used to step down the voltage from a battery and connect to microcontroller.